Occupational road safety worldwide: lessons for research, policy and practice. (1st March 2011) - Pratt, S; Murray, W; Townsend, E; Jackson, L L
Abstract : In February 2009, National Institute for Occupational Safety and Health (NIOSH) and partners hosted the first International Conference on Road Safety at Work, identifying the following for 200+ participants from 44 countries. Occupational motor vehicle crashes affect a substantial proportion of road and worker fatalities, meaning that occupationally focused initiatives can be highly significant. There is a consensus for the need to adopt a systems-based approach to at-work road safety, engaging all stakeholders. At the macro level, purpose of journey should be identified in road safety statistics, and on-road incidents should be included in health and safety datasets to guide policy, regulation and enforcement. Government leadership is also required by to manage the safety of their own employees. At the organisational level, it is important to make the business case for road safety and to ensure collection of data for baseline assessment and monitoring progress. These activities should be guided by a systems-led, risk-based approach and supported by rigorous evaluation. Further efforts are required to link research and practice, and continue to engage governments, researchers, practitioners and NGOs around the globe. Follow-up activities in Europe (already taking place through the ETSC PRAISE project), Asia, Africa and the emerging BRICK economies can sustain the energy and momentum generated by NIOSH. This paper describes these outcomes in detail, making recommendations for researchers, policy makers and practitioners; and identifying how barriers to success can be overcome, based on the conference white paper, proceedings and PRAISE project reports, including good practice cases from around the world.